2018
DOI: 10.1177/0002716217748591
|View full text |Cite
|
Sign up to set email alerts
|

“I Want to Be Trafficked so I Can Migrate!”: Cross-Border Movement of North Koreans into China through Brokerage and Smuggling Networks

Abstract: This article draws on ethnographic fieldwork and in-depth interviews with forty North Korean escapees involved in smuggling and brokerage networks and explores North Korean escapees’ cross-border mobility to China. It addresses the complexities of smuggling, showing how the category spans a continuum of actions that might be described as saving or rescuing at one pole, and the kind of exploitation generally termed trafficking at the other. By focusing on the multiple and varied interests and motivations of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Previous research indeed shows that male (sex) trafficking victims are more often than women in the same circumstances portrayed as "irregular migrants" who risk deportation, while female victims are more often seen as victims who need protection (Gallagher and Pearson 2010). These findings have important implications for the categorization and treatment of employees who work in exploitative conditions, especially because previous research shows that many victims of human trafficking and exploitation have at least partly contributed to their exploitation (Kook 2018;Schwarz 2019;Spencer 2015;Van Dijk 2009;Van Meeteren and Wiering 2019), and often do not want to portray themselves as vulnerable victims for various reasons (Dempsey 2011;Schwarz 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research indeed shows that male (sex) trafficking victims are more often than women in the same circumstances portrayed as "irregular migrants" who risk deportation, while female victims are more often seen as victims who need protection (Gallagher and Pearson 2010). These findings have important implications for the categorization and treatment of employees who work in exploitative conditions, especially because previous research shows that many victims of human trafficking and exploitation have at least partly contributed to their exploitation (Kook 2018;Schwarz 2019;Spencer 2015;Van Dijk 2009;Van Meeteren and Wiering 2019), and often do not want to portray themselves as vulnerable victims for various reasons (Dempsey 2011;Schwarz 2019).…”
Section: Discussionmentioning
confidence: 97%
“…From previous research we know that exploited persons often do not frame their experience as exploitation to protect their dignity or because they (or their families) are threatened (Schwarz 2019). Victims also often consent with exploitation, which does, however, not negate it (Kook 2018).…”
Section: The Role Of Labor Inspectors In the "State Agent" Narrativementioning
confidence: 99%
“…Difficulties in collecting data on traffickers could be another reason (Bhagat 2022). Despite an emerging body of research on brokers and brokerage in Asia and Nepal (Shrestha and Yeoh 2018;Kook 2018), there is a lack of nuanced research in the informal parts of the hospitality, entertainment, and wellness sectors. This study is one of a number of emerging studies on LIs and 'brokerage' that aim to 'open the black box of brokerage' (Axelsson et al 2022) and place these mediation practices in the context of informal, unregulated markets.…”
Section: Positioning Labour Intermediariesmentioning
confidence: 99%
“…Both the assumption of a single economic sector and the conception of a geographic location that is exclusive to these businesses and their workers is stigmatising. It also distracts from the available and emerging research on migration infrastructures, labour dynamics, and the complicated relationships between highly diverse workers and LIs(Shrestha and Yeoh 2018;Kook 2018). The researchers hope that this research helps to 'open the black box of brokerage'(Axelsson et al 2022).…”
mentioning
confidence: 99%
“…However, they have chosen to use such experiences to turn themselves into brokers for interested persons seeking their assistance. It was found that some victims present themselves willingly to be trafficked so that they can migrate (Kook, 2018). Wide age gap between the couples is apparent in this type of marriage migration, all in a bid for the vulnerable women migrant to acquire legal status in destination country and for profit for the brokers (Guetto and Azzolini, 2015;Elwert, 2016;Balistreri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%